Pengaruh Good Corporate Governance, Moralitas Individu, Dan Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi Pada Lpd Kabupaten Jembrana - Dewi, Ni Kade Febi Suryan; Martadinata, I Putu Hendra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2025)
This study aims to determine and examine the effect of Good Corporate Governance, Individual Morality, and Compensation Suitability on the tendency of accounting fraud in LPDs in Jembrana Regency. This study uses a quantitative approach with data collection through a questionnaire measured using a Likert scale. The population of this study were all LPDs in Jembrana Regency with a total of 62 LPDs and the sampling technique used purposive sampling so that 25 LPDs were obtained with 4 employees consisting of: (1) chairman, (2) secretary, (3) treasurer, (4) field officer of each Village Credit Institution (LPD) as respondents. Data analysis using SPSS version 25 (Software Statistical Package for the Social Sciences) through descriptive statistical analysis, data quality test, classical assumption test, and hypothesis testing. The results of this study indicate: (1) Good Corporate Governance has no effect on the tendency of accounting fraud, (2) Individual Morality has no effect on the tendency of accounting fraud, and (3) Compensation Suitability has no effect on the tendency of accounting fraud. This study shows that accounting fraud practices are not always significantly influenced by the elements in the fraud diamond theory, namely pressure (incentive/pressure), opportunity (oppportunity) rationalization (rationalization), and ability (capability). This finding strengthens the indication that there are other factors that are more dominant and relevant in explaining the tendency of fraud in LPDs. Thus, the application of fraud diamond theory needs to be considered contextually, as classic variables such as pressure, opportunity, rationalization, and capability may not always be relevant in every type of organization, especially those operating in communal social structures such as LPDs, and expanding the sample and research population.